PENGARUH KECERDASAN INTELEKTUAL DAN KREATIFITAS GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM PEMBELAJARAN TERHADAP HAFALAN AL-QUR’AN PESERTA DIDIK KELAS XI SMA DAARUL QUR’AN KOTA TANGERANG - Munawaroh, Munawaroh; Sudrajat, Sanin (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Intelligent learners will easily and quickly memorize the Qur'an, whereas learners of normal intelligence will have difficulty in memorizing the Qur'an and need a long time to complete the memorization of the Qur'an. In addition, the rote of learners can not be separated from the guidance of teachers, especially teachers tahfidz and teachers of Islamic Education (PAI) in learning. Creativity of PAI teachers in learning was expected to give a positive impact for the quality of memorization of Al-Qur'an learners. So according to researchers need to do research to prove that intellectual intelligence and creativity of PAI teachers in learning can influence or not to memorize Al-Qur'an learners in accordance with the purpose of this study. The method used in this study is descriptive analytical with quantitative approach that is to obtain or collect data, facts, and information related to the variables that the discussion of research (X1, X2 and Y). The sample of this research is 50 students of class XI SMA Daarul Qur'an Tangerang City with technique of sampling using random sampling technique (random sample). Then testing the hypothesis by using product moment formula with multiple correlation coefficient and multiple linear regression formula. Meanwhile, to determine whether or not the relationship or influence of variables X1, X2 and Y use the formula coefficient of determination, then to test the significance of each variable using t test formula and for multiple correlation using F test. The conclusion of this research is based on the result of the test of the research with product moment formula, then obtained the coefficient of double product moment correlation (Rx1x2y) is 0.60 and the coefficient of determination or determinant (KP) is 36%. Furthermore, it is proved also with t test result, obtained tcount> ttable that is 5,46> 2,021 for error level 5% (0,05) and Fth test result bigger than Ftable (13,23> 3,19). Thus, H0 rejected and Ha accepted means there is a positive influence together between intellectual intelligence and creativity of teachers PAI in learning to memorize Al Qur'an learners belonging to the interval coefficient with strong category (lies between 0,60-0,799).